The essence of financial uncertainty - Margarita K. Borodavina; Svetlana V. Rybakova; Anna V. Savina; Alina P. Khakhulina (Правоприменение)
The subject of the research is the concept and content of financial uncertainty as a new institution of financial law and, at the same time, a new phenomenon of financial and legal science.The purpose of the article is to determine the essence of financial uncertainty, to analyze the features and practical significance and identify factors that affect the occurrence of financial uncertainty.The methodology of the study includes methods of dialectical logic, analysis and synthesis, as well as formal legal analysis of legal acts.The main results and scope of their application. The financial uncertainty is a new institution of financial law and, at the same time, a new phenomenon of financial and legal science. Although the elements of financial uncertainty as the economic phenomenon are not new and are known to the practice of financial legal relations and the norms of financial legislation.Since the system of financial law is multi-spectral, especially in modern economic conditions, the institution of financial uncertainty, like many other institutions of financial law, is multifaceted and has its own characteristics in the framework of tax law, budget law, institutions of financial and legal regulation of banking and insurance, as well as other. For the general part of financial law, it is necessary to determine the definition of the concept of "financial uncertainty", its signs and elements. It is important to distinguish between the content of the institution of financial uncertainty in the legal regulation of fiscal interests of the state, as well as the interests of the state in public law regulation of finance of the private sector of the economy. In addition, to understand the problems of the institution of financial uncertainty in the subject of financial law, it is important to distinguish between financial and monetary relations. In all cases, the key, initial condition for scientific discourse is the risky nature of financial planning and forecasting. It is the principle of planning as one of the important principles of financial law that must be studied in the development of the desired institution.Conclusions. Financial uncertainty as a legal institution is complex because uncertainty and risks permeate the entire sphere of public financial activity: fiscal, parafiscal, monetary (including payment). In this regard, it can be argued that aspects of financial uncertainty relate, in fact, to each link of the financial, credit, monetary, and payment systems, and, accordingly, to each institution of a special part of financial law.